104 Characterisation Of The Proteome Of The Tendon Interfascicular Matrix. (5th September 2014) - Thorpe, Chavaunne; Peffers, Mandy; Simpson, Deborah; Halliwell, Elizabeth; Screen, Hazel; Clegg, Peter
Abstract : Introduction: Our previous work indicates that the interfascicular matrix (IFM) is critical for tendon function, facilitating sliding between fascicles to allow the tendon to stretch and recoil [Thorpe, 2012]. This is particularly important in energy storing tendons such as the human Achilles tendon and equine superficial digital flexor tendon (SDFT), which experience strains as high as 16% during exercise [Stephens, 1989], and therefore require the capacity for considerable inter-fascicular sliding. However, the composition of the IFM is poorly characterised, and little is known about which proteins within the IFM enable this sliding behaviour. Therefore, the aim of this study was isolate, characterise and compare the proteome of the IFM and fascicular matrix (FM) in the equine SDFT. We hypothesised that the proteomic profile would differ between the FM and the IFM, with greater complexity and turnover in the IFM. Methods: Sections from the mid-metacarpal region of grossly normal SDFTs (n = 10) were embedded in OCT and snap-frozen. Laser capture microdissection was used to isolate regions of the FM and IFM (Figure 1 ) from transverse cryosections. Following protein solubilisation and tryptic digestion, peptides were identified using liquid chromatography mass spectrometry (LC-MS/MS), using an Ultimate 3000 Nano system (Dionex/Thermo Fisher Scientific) on line to a Q Exactive Quadrupole-Orbitrap instrument (Thermo- Fisher Scientific). Proteins within the IFM and FM were identified using Peaks ® 7 Spider software, searching against the UniHorse database, with a false discovery rate (FDR) of 1%, a minimum of 2 peptides per protein and a confidence score > 50. Progenesis™ software was used to identify fold changes in protein abundance between the FM and IFM. Greater than 2 fold changes with FDR adjusted p values < 0.05 were considered to be significant. In addition, cleavage of matrix components was assessed by identification of non-tryptic peptides (neopeptides) in the FM and IFM. Results: A total of 246 proteins were identified in the IFM, and 141 in the FM (significance score >50). 60 proteins showed a > 2 fold change between the FM and IFM. Of these, 48 proteins were enriched in the IFM, including collagen type III, histones and ribosomal proteins. 12 proteins were at lower abundance in the IFM, including type I collagen, thrombospondin-1 and 4, cartilage oligomeric matrix protein (COMP) and fibromodulin. Neopeptides for collagens type I, III, V, XI, COMP and decorin were identified in both FM and IFM samples. A greater number of collagen neopeptides were identified in the IFM than in the FM. Discussion: This is the first work to provide a comprehensive analysis of proteins present within different regions of tendon. The data support our hypothesis, demonstrating a greater number of proteins within the IFM, and different levels of a large number of proteins between the FM and IFM. The higher levels of histones and ribosomal proteins are indicative of the greater cell number within the IFM. Despite lower abundance of collagens in the IFM, the greater number of collagen neopeptides identified in the IFM suggest the components of this matrix are turned over more rapidly than the FM. Further characterisation of the proteins within the IFM will provide a greater understanding of IFM and tendon function. Acknowledgements: Funded by BBSRC References: Stephens et al . Am J Vet Res.1989;50:1089–95 Thorpe et al . J R Soc Interface. 2012;9:3108–17